2021
DOI: 10.1186/s12870-021-03180-6
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genetic loci associated with major agronomic traits of wheat (Triticum aestivum L.) based on genome-wide association analysis

Abstract: Background Bread wheat (Triticum aestivum L.) is one of the most widely consumed cereal crops, but its complex genome makes it difficult to investigate the genetic effect on important agronomic traits. Genome-wide association (GWA) analysis is a useful method to identify genetic loci controlling complex phenotypic traits. With the RNA-sequencing based gene expression analysis, putative candidate genes governing important agronomic trait can be suggested and also molecular markers can be develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 67 publications
(65 reference statements)
0
8
0
Order By: Relevance
“…DNA was sent to the MOL-BREEDING Company (Shijiazhuang, China) for high-throughput genotyping using wheat GenoBaits technology (14868 mSNP, 37669 SNP). After eliminating markers with an allele frequency (MAF) < 0.05, > 10% missing data, or > 20% heterozygosity ( Arora et al, 2017 ; Jung et al, 2021 ), a total of 9,793 high-quality SNPs were identified for GWAS analyses ( Zheng et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…DNA was sent to the MOL-BREEDING Company (Shijiazhuang, China) for high-throughput genotyping using wheat GenoBaits technology (14868 mSNP, 37669 SNP). After eliminating markers with an allele frequency (MAF) < 0.05, > 10% missing data, or > 20% heterozygosity ( Arora et al, 2017 ; Jung et al, 2021 ), a total of 9,793 high-quality SNPs were identified for GWAS analyses ( Zheng et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…In our previous study (Jung et al, 2021), we used GWAS and RNAseq analysis and proposed that TaF‐box2 may be related to the flowering time of wheat. Increased expression of TaF‐box2 was observed until the late stage of floret development in wheat (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we observed that several F-box protein-coding genes were associated with spike maturity (Jung et al, 2021). Among them, TraesCS6A01G407500 (TaF-box2) showed particularly high gene expression in flowering-related tissues such as peduncle and spike.…”
Section: Expression Profile Of Taf-box2 At Different Stages Of Floret...mentioning
confidence: 98%
“…The appropriateness of the model used for association analysis in the present study was tested by drawing a QQ (quantile-quantile) plot between expected and observed -log10(P) values. The significance threshold was set by an application of an overall cut-off significance level of −log10 (P-value) ≥ 3.0, where one false positive was expected within 1,000 events ( Zanke et al., 2015 ; Jung et al., 2021 ). The QQ- and circular-Manhattan plots were drawn by the CMplot package in R ( Yin et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…None of these megaenvironments, however, is homogenous, but they represent rather rich combinations of various environmental factors ( Benaouda et al., 2022 ). The meteorological and climatic parameters of the location–especially the maximum temperatures in spring–play the most decisive roles in influencing plant development ( Jung et al., 2021 ; Benaouda et al., 2022 ). Thus, in addition to the two basic features, the determination of plant developmental patterns includes the sets of interconnected earliness per se genes that together ensure the fine-tuning of ecological adaptation ( Cockram et al., 2007 ; Griffiths et al., 2009 ; Dreisigacker et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%